2020
DOI: 10.1002/jemt.23474
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a root‐dentin pretreatment technique combining PIPS with MTAD aiming to improve the bond strength of glass fiber post

Abstract: The aim of this study was to evaluate the combined effect of MTAD and photon‐induced photoacoustic streaming (PIPS) technique on the smear layer removal and the bond strength of glass fiber post. Fifty‐five human mandibular premolars were chosen. After root canal therapy and post space preparation, the teeth were equally divided to five groups according to the methods of root‐dentin pretreatment: G1: distilled water (control); G2: 2.5% NaOCl+17% EDTA; G3: MTAD; G4: PIPS; G5: MTAD+PIPS. One sample was randomly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…19 PIPS technique on the other hand also possesses the ability to expose organic collagen fibers which results in the generation of an uneven and irregular root surface that permits the adhesive resin sealer to penetrate the dentin surface resulting in the enhancement of mechanical interlocking thus improving the bond strength of AH plus sealer. 9 Group-3 specimens treated with 2.25% NaOCl+PIPS +17% EDTA also exhibited comparable outcomes of bond integrity to that of 2.25% NaOCl+PIPS + 6.25% PPE treated samples. This is in line with the findings of the study conducted by Wen at el., 20 They identify the effect of PIPS using MTAD solution and suggested that the combination technique used is effective in getting rid of the smear layer.…”
Section: Groups Cervical Middle Apicalmentioning
confidence: 78%
See 2 more Smart Citations
“…19 PIPS technique on the other hand also possesses the ability to expose organic collagen fibers which results in the generation of an uneven and irregular root surface that permits the adhesive resin sealer to penetrate the dentin surface resulting in the enhancement of mechanical interlocking thus improving the bond strength of AH plus sealer. 9 Group-3 specimens treated with 2.25% NaOCl+PIPS +17% EDTA also exhibited comparable outcomes of bond integrity to that of 2.25% NaOCl+PIPS + 6.25% PPE treated samples. This is in line with the findings of the study conducted by Wen at el., 20 They identify the effect of PIPS using MTAD solution and suggested that the combination technique used is effective in getting rid of the smear layer.…”
Section: Groups Cervical Middle Apicalmentioning
confidence: 78%
“…The higher bond strength achieved by PPE than EDTA-treated specimens can be explained by the presence of a potentially active substance which improves smear layer removal and promotes bond strength. 21,22 It can also be stated that EDTA and PPE in combination with PIPS as a final irrigation protocol displayed better bond integrity than PPE and EDTA alone.…”
Section: Groups Cervical Middle Apicalmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of different solutions has been implemented to improve dentin conditioning and an effective remove of the SSL throughout the space created for the fiber post; these solutions include acid solutions, that is, ethylenediaminetetraacetic acid (EDTA) [10,25,34], OA [25,30,34], maleic acid [20], and citric acid at several concentrations such as 10%, 20%, and 50% [9,25]. Also, the use of several combined solutions allows a reduction of superficial tension, facilitating irrigants contact with dentinal walls, and enhancing SSL removal [35]; some examples are MTAD [34,36,37] and Q-mix [18,24]. There activity is summarized in Table 1.…”
Section: Conditioning Solutionsmentioning
confidence: 99%
“…Evidence shows that the bond strength to root canal wall depends on several factors(Wan et al, 2020) such as the root dentin properties, presence/absence of the smear layer, type and thickness of cement, type of bonding agent and its polymerization pattern, and the quality of endodontic treatment prior to post cementation with regard to the type and concentration of irrigating solution, sealer type, and so on(Niu et al, 2021). Similar to our findings, Gundugar et al reported an increase in the bond strength of EndoSequence bioceramic sealer to root dentin following the use of QMix.…”
mentioning
confidence: 99%